Perspectives from the Survey of Honey Bee Colony Losses During 2015–2016 in Argentina - Requier, Fabrice (2018)
Fil: Requier, Fabrice. Universidad Nacional de Río Negro. Sede Andina. Instituto de Investigaciones en Recursos Naturales, Agroecología y Desarrollo Rural (IRNAD); Argentina.